A history of the fossil fruits and seeds of the London Clay (1840): a historical and bibliographical account of James Scott Bowerbank's unfinished monograph. Issue 2 (October 2016) - Williams, R. B.; Torrens, Hugh S.
Abstract : A history of the fossil fruits and seeds of the London Clay by James Scott Bowerbank (1797–1877) was printed by George Luxford (1807–1854) and published by John Van Voorst (1804–1898). Part I was issued in 1840, before 6 January, but no more was published. The monograph, intended to comprise five parts, was apparently a commercial failure. Part I was originally issued in wrappers, without title-page or other preliminaries; it includes 17 copper-plate engravings by James de Carle Sowerby (1787–1871), the printer being unknown. A ghost work, the so-called "The fossil fruits and seeds of the Isle of Sheppey", cited occasionally in the contemporary literature, was in fact this monograph of Bowerbank's, not a separate publication. Twelve genera and 106 species are described, all new taxa except for one previously known species. Bowerbank apparently retained the unsold letterpress sheets until he died, after which they were bought by the publishers Reeves & Turner, who reissued them, possibly late in 1877. They added a title-page and, as an introduction, reprinted a letter about the Isle of Sheppey first published by Bowerbank in 1840. The plates were rather poorly reprinted from the original coppers by an unknown printer. The title-page of this scarce reissue does not name Reeves & Turner, but anachronistically gives Van Voorst as the publisher, still dated 1840. The present paper provides the historical and bibliographical background to these two issues of the sole edition, and describes their distinguishing features, determined from 18 copies of the original issue and eight copies of the reissue.